Case report: A cyclic neutropenia patient with ELANE mutation accompanied by hemophagocytic lymphohistiocytosis - Yu, Lang; Li, Yulin; Li, Wenhui; Zhang, Yishi; He, Wenli; Tang, Xuemei; An, Yunfei; Zhao, Xiaodong (Frontiers in Immunology, 2024)
Many inborn errors of immunity may accompany secondary hemophagocytic lymphohistiocytosis (HLH), a condition typically characterized by impaired cytotoxic T and NK cell function. A considerable proportion of HLH cases also stem from chronic granulomatosis with phagocytic dysfunction. However, the development of secondary HLH in patients with severe congenital neutropenia (SCN) or cyclic neutropenia (CyN) with abnormal phagocytic cell counts has been less frequently reported. Herein, we present a case of a pediatric patient with ELANE mutation-associated CyN who developed HLH subsequent to severe bacterial, fungal, and viral infections. Notable observations included impaired NK cell degranulation function (CD107a). To the best of our knowledge, this represents the first documented instance of HLH in patients with CyN attributed to an ELANE mutation. Thus, our study establishes a link between ELANE-related CyN and HLH, underscoring the importance of considering HLH as a potential complication in these patients.